2014
DOI: 10.3390/polym6122928
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Liquid Natural Rubber via Oxidative Degradation of Natural Rubber

Abstract: Natural rubber (NR) is a high molecular weight natural polymer and can be degraded to liquid natural rubber (LNR) leaving certain functional groups at the end of chains. In this study, LNR samples prepared via oxidative degradation using H2O2 and NaNO2 as reagents were found to have different end groups depending on the pH of the reaction medium. In an acidic medium, LNR with hydroxyl terminal groups was formed as the degradation reaction was initiated by hydroxyl radicals produced from decomposition of peroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 35 publications
(42 reference statements)
6
36
0
2
Order By: Relevance
“…Similar results could be obtained by chemical degradation of nonvulcanized NR. By oxidative degradation of NR latex using H 2 O 2 and NaNO 2 , Ibrahim et al [26] found that the LNR had different end groups, depending on the pH of the medium. In an acidic medium, NR with hydroxyl terminal groups was formed.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results could be obtained by chemical degradation of nonvulcanized NR. By oxidative degradation of NR latex using H 2 O 2 and NaNO 2 , Ibrahim et al [26] found that the LNR had different end groups, depending on the pH of the medium. In an acidic medium, NR with hydroxyl terminal groups was formed.…”
Section: Resultsmentioning
confidence: 99%
“…Spektra FTIR karet terhidrogenasi dibandingkan dengan karet alam murni disajikan pada Gambar 2. Dari Gambar 2 dapat diketahui bahwa spektra FTIR karet alam dicirikan oleh adanya serapan tajam pada puncak bilangan gelombang 1662 cm -1 (ikatan rangkap tak jenuh C=C, vibrasi ulur) dan 834 cm -1 (ikatan =C-H, vibrasi tekuk) (Ibrahim et al, 2014). Puncak serapan lain yang terdapat pada rantai molekul karet alam antara lain 2960 cm -1 (ikatan CH 3 , vibrasi ulur), 1446 cm -1 (ikatan CH 3 , vibrasi tekuk), 2850 cm -1 (ikatan CH 2 , vibrasi ulur), 1375 cm -1 (ikatan CH 2 , vibrasi tekuk), dan 739 cm -1 (ikatan -(CH 2 ) 3 ) (Mahittikul et al, 2007;Mahittikul et al, 2009;Arayapranee & Rempel, 2013).…”
Section: Hasil Dan Pembahasanunclassified
“…NR is classified as renewable and sustainable biopolymer, which is usually tapped and extracted from tropical rubber tree, known as Hevea brasiliensis. NR is extensively used in an enormous range of applications due to its high elongation, high elasticity, and resilience . Therefore, NR was used to improve the toughness properties of epoxy resins, because it is a renewable resource and is easily available in Malaysia …”
Section: Introductionmentioning
confidence: 99%